Feasibility of using textured die to improve or replace lubrication In microforming - Li, Joshua Fuhua. (2011)
The viability of using textured die to control friction in microforming was examined. A series of reciprocating ball on flat tribotests were carried out to simplify the approach of examining the friction behavior from an actual microforming setup.